Social Preferences and Planning Logics in Urban Water Adaptation - A Case Study of Pölen Pölen in Lund - Huggett,David (2025)
Transformation as an adaptation response can help align risk aversion practices with goals of sustainability and social justice. This lies in its ability to drive deep reaching changes in socio-environmental structures through critically examining and restructuring dominant power structures. This thesis applies Pelling et al’s (2015) transformative adaptation framework to a case-study of a technologically innovative adaptation measure at Pölen Pölen, in Lund. It investigates how social preferences within urban water management can affect the transition towards transformational climate resilience adaptation pathways in Lund’s municipality. A thematic analysis was conducted on interviews with key planning actors involved with the project, and a document analysis of newspaper articles and support planning documents. The results identified how dominant social preferences restricted the formation of transformative processes through established power-structures between the landowners and informal institutions such as student associations. The resulting adaptation measures were therefore aimed at maintaining the status-quo, and resisted changing a change in socio-environmental relations.
Keywords: Transformative Adaptation; Climate Resilience; Social Preferences; Urban Water Management